High efficiency bi-harvesting light/vibration energy using piezoelectric zinc oxide nanorods for dye decomposition. (August 2019) - Ma, Jiangping; Ren, Jing; Jia, Yanmin; Wu, Zheng; Chen, Lin; Haugen, Neale O.; Huang, Haitao; Liu, Yongsheng
Abstract: In this work, the bi-harvesting of light and vibration energy is realized in hydrothermally-synthesized ZnO nanorods which is designed to achieve photo-/piezo-bi-catalysis for dye decomposition. In the presence of both UV irradiation and vibration, the decomposition ratio of ZnO nanorods for acid orange 7 is ∼80.8% within 100 min, which is higher than the value of ∼56.7% for photo-catalysis or the value of ∼31.8% for piezocatalysis. The enhanced photo-/piezo-bi-catalysis of ZnO nanorods in dye decomposition can be attributed to that the piezoelectric potential which formed in piezocatalysis process can help separate the photogenerated electron-hole pairs, therefore achieving a synergy effect between photocatalysis and piezocatalysis. The excellent photo-/piezo-bi-catalysis of ZnO can potentially find application in enhancing catalytic efficiency of dye decomposition through harvesting the light and vibration energy present in natural environments. Graphical abstract: Image 1 Highlights: Bi-harvesting light/vibration energy using hydrothermally-synthesized ZnO nanorods is realized. Bi-catalysis for dye decomposition is better than photocatalysis or piezocatalysis alone. ZnO is potential for dye wastewater remediation through harvesting ambient light/vibration energy.